2020
DOI: 10.1186/s40104-019-0417-7
|View full text |Cite
|
Sign up to set email alerts
|

Net absorption and liver metabolism of amino acids and heat production of portal-drained viscera and liver in multiparous sows during transition and lactation

Abstract: Background Determination of nutrient requirements in the late gestating and lactating sows is essential to optimize sow productivity. The objectives of the present study were to quantify amino acid (AA) fluxes and heat production across portal-drained viscera (PDV) and liver in multiparous sows during transition and lactation. Methods Eight second parity sows were fitted with indwelling catheters in the femoral artery and in the mesenteric, portal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…We observed that several metabolic adaptations linked to the glucose–amino acid metabolic cross-road occurred to maintain glucose production under control following the HFHS meal, and this way better control glycaemia. Thus, as expected in the healthy animals, the gluconeogenic AA uptake by the liver was inhibited (yet still present as shown by previous studies on pigs [ 32 ]) following the meal: a mechanism that was no longer observed when these same animals became obese. Interestingly, these AA were indeed taken up, as the latter occurred in the insulin resistant state [ 33 ] and in line with the concomitant larger release of gluconeogenic AA by the intestine.…”
Section: Discussionsupporting
confidence: 76%
“…We observed that several metabolic adaptations linked to the glucose–amino acid metabolic cross-road occurred to maintain glucose production under control following the HFHS meal, and this way better control glycaemia. Thus, as expected in the healthy animals, the gluconeogenic AA uptake by the liver was inhibited (yet still present as shown by previous studies on pigs [ 32 ]) following the meal: a mechanism that was no longer observed when these same animals became obese. Interestingly, these AA were indeed taken up, as the latter occurred in the insulin resistant state [ 33 ] and in line with the concomitant larger release of gluconeogenic AA by the intestine.…”
Section: Discussionsupporting
confidence: 76%
“…The sows were artificially inseminated with DanBred Duroc semen (Hatting KS, Horsens, Denmark) resulting in Danish Landrace × Yorkshire × Duroc progeny. The feeding strategy of sows and management procedures were described in detail by Hu et al (2020). Piglets were weighed and enriched with deuterium oxide (D 2 O) at day 28 (weaning).…”
Section: Animals and Experimental Procedures-expmentioning
confidence: 99%
“…Energy and nutrients ATTD were calculated as described by Stein et al [23]. Plasma flows and blood flows in the portal vein, hepatic vein and the hepatic artery as well as net portal flux (NPF), net hepatic flux (NHF), net portal recovery, and hepatic extraction were calculated according to Hu et al [24]. HMB intake (g/d) = sow BW × 0.015 × 0.808, where 0.015 corresponds with 15 mg/kg BW and 0.808 accounts for HBM content in Ca(HMB) 2 • 1 H 2 O (molar mass = 292.35 g/mol), and when converting into mmol/L or mmol/h, 2 mol of HMB for each mole of Ca(HMB) 2 was taken into account.…”
Section: Calculations and Statistical Analysismentioning
confidence: 99%